A protective layer modified zinc negative electrode material and its preparation method and application

By forming a chemical crosslinked polymer protective layer between zwitterionic substances and hydrophilic monomers on the zinc negative electrode material, the problem of unstable zinc negative electrodes in aqueous batteries is solved, and the uniform distribution of zinc ions and improvement of battery performance is achieved. , suitable for large-scale production.

CN114725336BActive Publication Date: 2025-01-14WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210260059.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-16
Publication Date
2025-01-14
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

In rechargeable aqueous zinc ion batteries, the metal zinc negative electrode is thermodynamically unstable in the aqueous electrolyte and is easily subjected to water-oxygen corrosion, resulting in the formation of zinc dendrites and the efficiency of Coulombs. The existing modification methods are complex and costly.

Method used

The chemical crosslinked polymer protective layer formed by radical polymerization of zwitterionic substances and hydrophilic monomers is used to modify the zinc negative electrode material, inhibit dendrites' growth and corrosion, and prevent zinc foil corrosion by uniformly distributing zinc ions and attracting water molecules.

Benefits of technology

It achieves good cycle stability and rate performance of zinc negative electrode materials, extends service life, simplifies the preparation process, reduces costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114725336B_ABST
    Figure CN114725336B_ABST
Patent Text Reader

Abstract

The present invention relates to a protective layer-modified zinc negative electrode material and a preparation method and application thereof. The zinc negative electrode material is a zinc-containing metal substrate coated with a protective layer, and the preparation method has the following steps: 1) adding a zwitterionic substance, a hydrophilic monomer, and an oxidant to a solvent, and stirring evenly at room temperature to obtain a slurry; 2) adding a catalyst to the slurry, stirring evenly to obtain a precursor liquid, exhausting the precursor liquid and evenly coating it on the zinc-containing metal substrate, and then leaving it at room temperature. After the precursor liquid polymerizes on the zinc-containing metal substrate, the obtained sample is vacuum dried to obtain a protective layer-modified zinc negative electrode material. The surface of the zinc negative electrode material provided by the present invention is modified with a functional zwitterionic interface layer, and the modified interface can guide the zinc ions to be evenly distributed on the surface of the metal zinc, and accelerate the Zn 2+ Diffusion of Zn 2+ Uniform nucleation and efficient deposition give zinc negative electrode materials good cycle stability and rate performance, long service life and greater safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrodes composed of zinc-based alloys, and in particular relates to a protective layer-modified zinc negative electrode material and a preparation method and application thereof. Background Art

[0002] With the continuous development of rechargeable secondary battery technology, people have put forward higher requirements for the safety and environmental performance of batteries. The currently widely used lithium-ion batteries are hindered from further development due to their low element reserves, high cost and poor safety. Rechargeable aqueous zinc-ion batteries have become a favorable candidate to replace lithium-ion batteries due to their high element reserves, low cost and high safety.

[0003] However, there are still some urgent problems to be solved in rechargeable aqueous zinc-ion batteries. The metal zinc negative electrode is thermodynamically unstable in the aqueous electrolyte and will suffer from severe water-oxygen corrosion, producing a large amount of byproducts such as zinc hydroxysulfate. Zinc will tend to nucleate at positions with lower energy, thus forming zinc dendrites. Some dendrites will break to form dead zinc, resulting in a decrease in coulombic efficiency. The continuously growing zinc dendrites may even pierce the diaphragm, causing the battery to fail.

[0004] In order to solve the above problems, people have carried out a lot of work, such as constructing three-dimensional electrode structures to regulate zinc ion flux and promote uniform deposition of zinc ions; preparing high-concentration electrolytes, using electrolyte additives, etc. However, these methods are limited by complex preparation processes and high costs. Coating a functional layer on the surface of metallic zinc is a simple and effective method. At present, coatings such as graphene, metal nanoparticles, and inorganic nanoparticles have been widely studied. However, the weak adsorption and brittleness of this type of coating with metallic zinc make it easy to fall off when the volume expands due to electrochemical reactions. Considering the adhesion and mechanical adaptability of polymers, combining inorganic and organic is a feasible strategy. For example, PVDF and TiO 2 However, nanoparticles tend to aggregate in polymer solvents and are not easily dispersed in organic solvents, which can lead to failure in the precise transmission of zinc ions. Therefore, it is urgent to prepare an environmentally friendly zinc negative electrode material that can inhibit zinc dendrites to achieve large-scale production of aqueous zinc ion batteries. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, one of the objectives of the present invention is to provide a zinc negative electrode material modified with a protective layer.

[0006] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:

[0007] A protective layer-modified zinc negative electrode material, wherein the zinc negative electrode material is a zinc-containing metal substrate coated with a protective layer, and the preparation method thereof comprises the following steps:

[0008] 1) adding a zwitterionic substance, a hydrophilic monomer, and an oxidant into a solvent, and stirring at room temperature to obtain a slurry;

[0009] 2) Add a catalyst to the slurry obtained in step 1), stir evenly to obtain a precursor solution, exhaust the precursor solution and evenly coat it on a zinc-containing metal substrate, then place it at room temperature (15-35° C.), wait for the precursor solution to polymerize on the zinc-containing metal substrate, and then vacuum dry the obtained sample to obtain a zinc negative electrode material modified with a protective layer.

[0010] According to the above scheme, the thickness of the protective layer is 5 to 30 μm.

[0011] According to the above scheme, the zinc-containing metal substrate is zinc foil with a thickness of 30 to 150 μm.

[0012] According to the above scheme, the zwitterionic substance in step 1) is a carboxylic acid zwitterion or a sulfonic acid zwitterion;

[0013] The carboxylic acid type zwitterion is one of 5-(2-methacryloyloxyethyldimethylamino)pentanoic acid inner salt, 5-(acryloyloxyethyldimethylamino)pentanoic acid inner salt, 3-(2-methacryloyloxyethyldimethylamino)propanoic acid inner salt, 3-(acryloyloxyethyldimethylamino)propanoic acid inner salt, 2-(2-methacryloyloxyethyldimethylamino)ethyl carboxylic acid inner salt, 2-(acryloyloxyethyldimethylamino)ethyl carboxylic acid inner salt, and 1-vinyl-3-carboxymethylimidazole;

[0014] The sulfonic acid zwitterion is N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt or 3-(acryloyloxyethyl dimethylamino) propanesulfonic acid inner salt.

[0015] According to the above scheme, the hydrophilic monomer in step 1) is selected from one or more of acrylic acid, acrylamide, methyl methacrylate, ethylene glycol, and methacrylic acid.

[0016] According to the above scheme, the oxidant in step 1) is selected from one of sodium persulfate, ammonium persulfate, potassium persulfate, azobisisobutyronitrile, and cerium ammonium nitrate.

[0017] According to the above scheme, the solvent in step 1) is selected from one of deionized water, dimethyl sulfoxide, ether, ethanol, methanol, dichloromethane, chloroform, toluene, acetone and isopropanol.

[0018] According to the above scheme, in step 1), the molar ratio of the zwitterionic substance to the hydrophilic monomer is 1:2-5; the mass ratio of the total mass of the zwitterionic substance and the hydrophilic monomer to the oxidant is 1:0.005-0.03; the mass ratio of the total mass of the zwitterionic substance and the hydrophilic monomer to the solvent is 1-5:10.

[0019] According to the above scheme, the catalyst in step 2) is selected from one of tetramethylethylenediamine, triethylamine, N,N-dimethylcyclohexylamine, triethylenediamine, and triethylenediamine. The catalyst initiates the oxidant to form free radicals, which initiate the polymerization of zwitterionic monomers and acrylamide monomers to form a protective layer.

[0020] According to the above scheme, the ratio of the mass of the catalyst in step 2) to the total mass of the zwitterionic substance and the hydrophilic monomer in the slurry is 0.005-0.02:1.

[0021] According to the above scheme, the room temperature placement time in step 2) is 10 to 60 minutes.

[0022] According to the above scheme, the vacuum drying temperature in step 2) is 40 to 80° C., and the vacuum drying time is 6 to 12 hours.

[0023] A second object of the present invention is to provide a method for preparing the above-mentioned protective layer modified zinc negative electrode material.

[0024] The specific technical solutions are as follows:

[0025] A method for preparing the above-mentioned protective layer modified zinc negative electrode material, the specific steps are as follows:

[0026] 1) adding a zwitterionic substance, a hydrophilic monomer, and an oxidant into a solvent, and stirring at room temperature to obtain a slurry;

[0027] 2) Adding a catalyst to the slurry obtained in step 1), stirring evenly to obtain a precursor solution, exhausting the precursor solution and evenly coating it on a zinc-containing metal substrate, then leaving it at room temperature, after the precursor solution polymerizes on the zinc-containing metal substrate, vacuum drying the obtained sample to obtain a zinc negative electrode material modified with a protective layer.

[0028] The third object of the present invention is to provide the application of the zinc negative electrode material modified with the above protective layer.

[0029] The specific technical solutions are as follows:

[0030] An application of the above protective layer modified zinc negative electrode material in aqueous zinc ion batteries.

[0031] A fourth object of the present invention is to provide an aqueous zinc ion battery prepared according to the zinc negative electrode material modified with the above-mentioned protective layer.

[0032] The principle of the present invention is as follows:

[0033] The present invention suppresses the side reactions that may occur, such as dendrite growth, corrosion, etc., by preparing a functional modification layer on the zinc negative electrode. The modification layer is a polymer protective layer with a chemical cross-linking structure formed by free radical polymerization of zwitterionic substances and hydrophilic monomers. The zwitterionic functional groups in the protective layer can effectively promote the uniform distribution of zinc ions at the interface between the electrolyte and the zinc negative electrode, thereby effectively regulating the uniform deposition of zinc and suppressing the growth of dendrites. At the same time, the zwitterions in the modification layer will attract a large number of water molecules, hindering the direct contact between active water and zinc foil, which is beneficial to prevent the active water in the electrolyte from corroding the zinc negative electrode and generating byproducts.

[0034] The beneficial effects of the present invention are as follows: 1. The surface of the zinc negative electrode material provided by the present invention is modified with a functional zwitterionic interface layer, and the modified interface can guide the zinc ions to be evenly distributed on the surface of the metal zinc and accelerate the Zn 2+ Diffusion of Zn 2 + Uniform nucleation and efficient deposition make the zinc negative electrode material have good cycle stability and rate performance, long service life and greater safety. 2. The preparation method provided by the present invention is relatively simple to operate, short synthesis time, mild reaction conditions, low cost, green and environmentally friendly, good repeatability, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The SEM images of the plane and cross section of the PZIL-Zn pole piece prepared in Example 1 of the present invention;

[0036] Figure 2 The surface of the PZIL-Zn electrode prepared in Example 1 and the initial raw material zinc foil were 2 mol L -1 ZnSO 4 Contact angle photographs of aqueous solutions;

[0037] Figure 3 This is a cycle life test diagram of a symmetrical battery assembled from the PZIL-Zn pole piece in Example 1 and a symmetrical battery assembled from the initial raw material zinc foil;

[0038] Figure 4 The symmetrical battery assembled from the PZIL-Zn pole piece in Example 1 and the symmetrical battery assembled from the initial raw material zinc foil at 8 mA cm -2 Cycle life test diagram under high current density;

[0039] Figure 5 This is a rate performance test diagram of a symmetrical battery assembled from the PZIL-Zn pole piece in Example 1 and a symmetrical battery assembled from the initial raw material zinc foil;

[0040] Figure 6The symmetrical battery assembled from the PZIL-Zn pole piece in Example 1 and the symmetrical battery assembled from the initial raw material zinc foil at 1 mA cm -2 Current density and 1mAh cm -2 Scanning images of the cross section of the initial raw material zinc foil and PZIL-Zn electrode after 100 cycles at surface capacity;

[0041] Figure 7 The symmetrical battery assembled from the PZIL-Zn pole piece in Example 1 is 1 mA cm -2 Current density and 1mAh cm -2 Scanning image of the cross section of the PZIL-Zn electrode after 100 cycles at areal capacity;

[0042] Figure 8 The symmetrical battery assembled from the PZIL-Zn pole piece in Example 1 and the symmetrical battery assembled from the initial raw material zinc foil at 1 mA cm -2 Current density and 1mAh cm -2 XRD patterns of the initial raw material zinc foil and PZIL-Zn electrode after 100 cycles at areal capacity;

[0043] Fig. 9 This is an optical photograph of the soft-pack battery assembled in Example 1. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0045] Example 1

[0046] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0047] 1.2 g of acrylamide and 0.64 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 18.4 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 18.4 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil (the zinc foil was a disc with a thickness of 100 μm and a diameter of 10 cm) at a spin coating speed of 3000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material (denoted as PZIL-Zn pole piece).

[0048] Figure 1These are SEM images of the plane and cross section of the PZIL-Zn pole piece prepared in this embodiment. It can be seen that the thickness of the modified layer is about 9.8 μm.

[0049] Figure 2 The surface of the PZIL-Zn electrode and the initial raw material zinc foil prepared in this embodiment is 2 mol L -1 ZnSO 4 The contact angle photo of the aqueous solution shows that the contact angle between the electrolyte and the initial raw material zinc foil is 103°. In comparison, the contact angle between the electrolyte and PZIL-Zn is 66°, indicating that the PZIL protective layer greatly increases the hydrophilicity of the zinc foil surface. Better hydrophilicity is conducive to uniform contact between the electrolyte and the zinc negative electrode, which is conducive to reducing impedance.

[0050] The PZIL-Zn pole pieces prepared in this example were assembled into symmetrical batteries, and the electrolyte used was 2 mol / L ZnSO 4 The symmetrical battery was tested at 1 mA cm -2 Current density and 1mAh cm -2 The long cycle performance under surface capacity is compared with the symmetrical battery assembled with the initial raw material zinc foil (Bare Zn). Figure 3 This is a test chart of the cycle life of two symmetrical batteries. The symmetrical battery assembled with the initial raw material zinc foil short-circuited after 84 hours of cycling, while the symmetrical battery assembled with PZIL-Zn could stably cycle for 2600 hours, which shows that the PZIL protective layer can greatly increase the service life of the zinc negative electrode.

[0051] The PZIL-Zn pole pieces prepared in this example were assembled into symmetrical batteries, and the electrolyte used was 2 mol / L ZnSO 4 Solution, tested symmetrical battery at 8 mA cm -2 The current density and 8 mAh cm -2 The long cycle performance under surface capacity is compared with the symmetrical battery assembled with the initial raw material zinc foil. Figure 4 For two symmetrical cells at 8 mA cm -2 The cycle life test diagram under high current density shows that the symmetrical battery assembled with the initial raw material zinc foil quickly short-circuited, while the symmetrical battery assembled with PZIL-Zn can still cycle stably for 300 hours, indicating that the PZIL protective layer can also play a good protective role under high current density.

[0052] The PZIL-Zn pole pieces prepared in this example were assembled into symmetrical batteries, and the electrolyte used was 2 mol / L ZnSO 4 Solution, tested symmetrical cells at 0.2, 0.5, 1, 2, 5, 10 mA cm -2The rate performance at the current density is compared with the symmetrical battery assembled with the initial raw material zinc foil. Figure 5 The figure is a test diagram of the rate performance of two symmetrical batteries. The test results show that the voltage polarization of the initial raw material zinc foil changes suddenly during the current increase, which means that the unmodified bare zinc cannot withstand the sudden change of current due to its weaker ion transport. In contrast, because the PZIL layer is conducive to the rapid transport of ions, PZIL-Zn has better rate performance.

[0053] The PZIL-Zn pole pieces prepared in this embodiment were assembled into a symmetrical battery and compared with a symmetrical battery assembled from the initial raw material zinc foil. Figure 6 For both batteries at 1 mA cm -2 Current density and 1mAh cm -2 Scanning images of the cross-section of the initial raw material zinc foil and PZIL-Zn electrode after 100 cycles at surface capacity. The SEM image on the left shows the surface of the initial raw material zinc foil after 100 cycles. It can be seen from the figure that there are a large number of zinc dendrites on the surface of the pure zinc foil electrode after the cycle. The large growth of dendrites will cause the battery to short-circuit. The SEM image on the right shows that the surface of the PZIL-Zn electrode is flat after the cycle, without dendrites and by-products.

[0054] The symmetrical battery assembled with the PZIL-Zn pole piece prepared in this embodiment, Figure 7 For this symmetrical battery at 1 mA cm -2 Current density and 1mAh cm -2 Scanning image of the cross section of the PZIL-Zn electrode after 100 cycles at surface capacity. The left image is a cross-sectional SEM image of the PZIL-Zn after cycling. It can be seen that zinc is uniformly deposited under the PZIL layer. In order to more intuitively observe the deposition morphology of zinc, the PZIL layer was removed for further observation. The SEM image on the right shows the deposition morphology of zinc after the PZIL layer was removed. It can be intuitively observed that zinc is uniformly and densely deposited under the PZIL layer, indicating that the PZIL layer can regulate the deposition behavior of zinc ions, avoid the formation of zinc dendrites, and greatly improve the cycle life of the zinc negative electrode.

[0055] The PZIL-Zn pole pieces prepared in this example were assembled into a symmetrical battery and compared with a symmetrical battery assembled with the initial raw material zinc foil. -2 Current density and 1mAh cm -2 The XRD patterns of the initial raw material zinc foil and PZIL-Zn electrode after 100 cycles at the surface capacity are shown in Figure 2. Figure 8 As shown in the figure, it can be seen that Zn 4 (OH) 6 SO 4 ·4H 2O byproducts were generated, while no byproducts were generated on the surface of PZIL-Zn, indicating that PZIL effectively prevented the active water in the electrolyte from corroding the zinc anode.

[0056] The PZIL-Zn pole piece prepared in this embodiment is assembled into a soft-pack battery, with manganese dioxide as the positive electrode and the PZIL-Zn pole piece as the negative electrode. Fig. 9 Optical photos of assembled soft-pack batteries. The left picture shows that the assembled soft-pack battery shows an open circuit voltage of 1.44V, and two soft-pack batteries can be successfully connected in series. The middle picture shows that the soft-pack batteries in series can successfully light up the LED lamp, and the right picture shows that the soft-pack battery can work stably even under bending conditions, indicating that PZIL-Zn has good flexibility and can work stably under actual working conditions.

[0057] Example 2

[0058] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0059] 1.2 g of acrylamide and 0.51 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 17.1 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 17.1 mg of tetramethylethylenediamine was dropped into the solution with a pipette and stirred for 2 min to evenly disperse the precursor solution. The precursor solution was placed in a vacuum box to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The evenly coated zinc foil was then allowed to stand for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0060] Example 3

[0061] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0062] 1.2 g of acrylamide and 0.85 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 20.5 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 20.5 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0063] Example 4

[0064] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0065] 1.2 g of acrylamide and 1.28 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 24.8 mg of ammonium persulfate was added to the above solution and stirred for 30 min to obtain a slurry. Then, 24.8 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The evenly coated zinc foil was then allowed to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0066] Example 5

[0067] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0068] 1.2 g of acrylamide and 0.64 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 18.4 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 18.4 mg of tetramethylethylenediamine was dropped into the solution with a pipette and stirred for 2 min to disperse it evenly to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 4000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a zinc negative electrode material modified with a protective layer.

[0069] Example 6

[0070] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0071] 1.2 g of acrylamide and 0.64 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 18.4 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 18.4 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 6000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0072] Example 7

[0073] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0074] 1.2 g of acrylamide and 0.64 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 18.4 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 18.4 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 60 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0075] Example 8

[0076] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0077] 1.2 g of acrylamide and 0.64 g of 1-vinyl-3-carboxymethylimidazole powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 18.4 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 18.4 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 90 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0078] Example 9

[0079] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0080] 1.2 g of acrylamide and 2.36 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 35.6 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 35.6 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0081] Example 10

[0082] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0083] 1.2 g of acrylamide and 1.57 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 27.7 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 27.7 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0084] Embodiment 11

[0085] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0086] 1.2 g of acrylamide and 1.18 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 23.8 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 23.8 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0087] Example 12

[0088] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0089] 1.2 g of acrylamide and 0.94 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 21.4 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 21.4 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 3000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0090] Embodiment 13

[0091] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0092] 1.2 g of acrylamide and 1.18 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 23.8 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 23.8 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 4000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0093] Embodiment 14

[0094] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0095] 1.2 g of acrylamide and 1.18 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 23.8 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 23.8 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 6000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0096] Embodiment 15

[0097] A protective layer-modified zinc negative electrode material, the preparation method of which comprises the following steps:

[0098] 1.2 g of acrylamide and 1.18 g of N,N-dimethyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt powder were added to 10 mL of deionized water and stirred at room temperature for 30 min until the monomer was dissolved. Then, 23.8 mg of ammonium persulfate was added to the above solution and stirred for another 30 min to obtain a slurry. Then, 23.8 mg of tetramethylethylenediamine was dropped into it with a pipette and stirred for 2 min to make it evenly dispersed to obtain a precursor solution. The precursor solution was placed in a vacuum box and evacuated to remove bubbles. 1 mL of the precursor solution was spin-coated on a zinc foil at a speed of 8000 r / s for 30 s. The spin-coated zinc foil was then left to stand at room temperature for 30 min. After the precursor solution was polymerized on the zinc-containing metal substrate, the obtained sample was placed in a vacuum oven at 60°C and dried for 6 hours to obtain a protective layer-modified zinc negative electrode material.

[0099] For those skilled in the art, various corresponding changes and modifications can be made according to the above technical solutions and concepts, and all of these changes and modifications should be included in the protection scope of the claims of the present invention.

Claims

1. A protective layer modified zinc negative electrode material, characterized in that, The zinc negative electrode material is a zinc-containing metal substrate coated with a protective layer, and the preparation method thereof is as follows: 1) adding zwitterionic substances, hydrophilic monomers and oxidants into a solvent and stirring at room temperature to obtain a slurry; 2) adding a catalyst to the slurry obtained in step 1), stirring evenly to obtain a precursor solution, exhausting the precursor solution and evenly coating it on a zinc-containing metal substrate, then leaving it at room temperature, and after the precursor solution polymerizes on the zinc-containing metal substrate, vacuum drying the obtained sample to obtain a zinc negative electrode material modified with a protective layer; Step 1) the zwitterionic substance is a carboxylic acid zwitterionic substance; The carboxylic acid zwitterion is 1-vinyl-3-carboxymethylimidazole; Step 1) the hydrophilic monomer is selected from one or more of acrylic acid, acrylamide, methyl methacrylate, and methacrylic acid; Step 1) the oxidant is selected from one of sodium persulfate, ammonium persulfate, potassium persulfate, azobisisobutyronitrile and cerium ammonium nitrate; Step 1) the solvent is selected from one of deionized water, dimethyl sulfoxide, ether, ethanol, methanol, dichloromethane, chloroform, toluene, acetone and isopropanol; Step 2) The catalyst is selected from one of tetramethylethylenediamine, triethylamine, N,N-dimethylcyclohexylamine, triethylenediamine and triethylenediamine.

2. The protective layer modified zinc negative electrode material according to claim 1, characterized in that: The protective layer has a thickness of 5 to 30 μm; the zinc-containing metal substrate is zinc foil with a thickness of 30 to 150 μm.

3. The protective layer modified zinc negative electrode material according to claim 1, characterized in that: Step 1) The molar ratio of the zwitterionic substance to the hydrophilic monomer is 1:2-5; the mass ratio of the total mass of the zwitterionic substance and the hydrophilic monomer to the oxidant is 1:0.005-0.03; the mass ratio of the total mass of the zwitterionic substance and the hydrophilic monomer to the solvent is 1-5:

10.

4. The protective layer modified zinc negative electrode material according to claim 1, characterized in that: Step 2) The ratio of the mass of the catalyst to the total mass of the zwitterionic substance and the hydrophilic monomer in the slurry is 0.005-0.02:

1.

5. The protective layer modified zinc negative electrode material according to claim 1, characterized in that: The room temperature placement time of step 2) is 10-60 minutes; the vacuum drying temperature of step 2) is 40-80° C., and the vacuum drying time is 6-12 hours.

6. A method for preparing a protective layer-modified zinc negative electrode material according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: 1) adding zwitterionic substances, hydrophilic monomers and oxidants into a solvent and stirring at room temperature to obtain a slurry; 2) Add a catalyst to the slurry obtained in step 1), stir evenly to obtain a precursor solution, exhaust the precursor solution and evenly coat it on a zinc-containing metal substrate, then leave it at room temperature. After the precursor solution is polymerized on the zinc-containing metal substrate, vacuum dry the obtained sample to obtain a zinc negative electrode material modified with a protective layer.

7. Use of the protective layer modified zinc negative electrode material according to any one of claims 1 to 5 in an aqueous zinc ion battery.

8. An aqueous zinc ion battery prepared according to the protective layer modified zinc negative electrode material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of novel polyamide composite separation membrane

    CN103990385A

  • Elastic low-temperature-resistant solid electrolyte and preparation method thereof

    CN113258145A

  • Zinc negative pole piece and preparation method and application thereof

    CN113690397A